Preparation method of structural color coating
Monodisperse nanoparticle clusters are prepared through spray drying equipment and mixed with organic gel to form a composite coating, which solves the problem of poor mechanical stability of colloidal photonic crystal structure color coatings and achieves high adhesion, wash resistance and green environmental protection. Structural color coating.
Patent Information
- Application Number
- CN202411464170.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The existing colloidal photonic crystal structure color coating has poor mechanical stability, is easy to fall off, and is easily affected by the environment to cause damage and color loss, which limits its practical application.
Use spray drying equipment to prepare a single-decentralized nanoparticle cluster, and mix with organic gel premature clusters, curing agents and light-absorbing materials to form a composite coating of organic gel-nanoparticle cluster. Structural color coating.
The mechanical stability, chemical stability and scrub resistance of the coating are achieved, and the coating adhesion reaches level 1 or above, and the integrity is maintained under high-frequency scrubbing, meeting the requirements of green and sustainable development.
Smart Images

Figure CN119350963A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a structural color coating, in particular to a method for preparing an organic gel-nano particle cluster composite coating with angle-independent structural color. Background Art
[0002] As an optical material with periodic and ordered micro-nano structures, photonic crystals can selectively control the propagation of photons with their own micro-nano structures, producing stable and bright structural colors. This color generated by the structure does not have the problems of photooxidation and photobleaching common in chemical dyes. At the same time, structural colors also avoid environmental pollution caused by chemical dyeing, and have broad application prospects in the fields of pattern printing, optical display and sensor detection. Among them, colloidal photonic crystals are a type of optical microstructure material formed by self-assembly of monodisperse colloidal particles. Compared with photonic crystals constructed by mechanical processing, laser etching and other means, colloidal photonic crystals have attracted widespread attention in many fields, especially in color-related fields, due to their universality, controllability, low cost and easy functional modification. Researchers have long been committed to developing colorful colloidal photonic crystal coatings for decorating fabrics, cars and buildings.
[0003] The weak particle-particle and particle-substrate interactions in the colloidal photonic crystal structure result in poor mechanical stability of the prepared structural color coating and easy detachment, which seriously hinders the practical application of the structural color coating. In addition, these structural color coatings are extremely susceptible to environmental influences, and the wetting of liquids and mechanical friction will cause damage and discoloration of the coating. In order to solve the problems of poor mechanical stability and limited application of structural color coatings, relevant researchers have made many efforts. For example, patent CN107201690 B uses functionalized modified polystyrene or polymethyl methacrylate monodisperse colloidal particles as building units, and discloses a method for preparing structural color coatings using monodisperse colloidal particles. By introducing functional groups such as carboxyl, amino and hydroxyl groups on the surface of the particles during the synthesis of the colloidal particles, the assembly force between the particles is increased, thereby achieving a stable structure and a large area of crack-free structural color coating. However, due to the limitations of the synthesis means and process, this method is difficult to expand on a large scale. In addition, pure particle-based coatings are difficult to withstand high-intensity washing and friction, which limits their further application. Patent CN 104725919 B discloses a method for preparing a hydrophobic structural color coating, wherein a cationic hydrophobic agent is used to coat a photonic crystal film assembled from anionic monodisperse nanoparticles. Under the protection of the hydrophobic coating, the colloidal photonic crystal coating can be protected from damage by the external environment. Although this method achieves a structural color coating with bright colors and stable mechanical properties, it often requires multiple steps to complete, has many restrictions, is time-consuming and labor-intensive, and due to the asymmetry of the assembly structure, the constructed structural color coating exhibits an iridescent effect. Patent CN 114958182A discloses a method for preparing a structural color coating using waterborne polyurethane as an auxiliary film-forming component, wherein a flexible long-chain polymer with rich functional groups is used as an auxiliary film-forming component, and the mechanical stability of the structural color coating is greatly improved by crosslinking and coating the colloidal particles. However, the flexible long chain interrupts the assembly order of the colloidal particles, and the colloidal particles tend to assemble into a non-crystalline photonic structure with long-range disorder but short-range order. This amorphous photonic structure often produces a large amount of incoherent light scattering, resulting in the structural color being whitish and having low color saturation.
[0004] Therefore, considering practical applications, it remains a huge challenge to improve the comprehensive application performance of structural color coatings while maintaining the highly ordered assembly structure of colloidal photonic crystals and to develop colloidal photonic crystal coatings with bright non-iridescent structural colors, stable mechanical properties and good washability. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a structural color coating. The coating prepared by the method has good mechanical stability, chemical stability and washability, and can be widely used in the decoration and protection of the surface of substrates such as metals, plastics, glass and cloth. The present invention provides an organic gel-nanoparticle composite coating that can present uniform and bright angle-independent structural colors. The preparation method of the coating is simple and does not require special post-treatment. In addition, the coating does not emit VOCs into the atmosphere during the curing film-forming process, meeting the requirements of green and sustainable development.
[0006] The present invention is mainly realized by the following technical scheme: a method for preparing a structural color coating, the specific steps of which are as follows:
[0007] a. Preparation of monodisperse nanoparticle clusters: using a spray drying device to quickly remove the solvent in the monodisperse nanoparticle dispersion to obtain spherical monodisperse nanoparticle clusters distributed in micrometer scale; wherein,
[0008] The parameters of the spray drying equipment were set as 100-130°C inlet temperature, 10-30mL / h peristaltic pump feed rate, and 30-50L / h air flow rate;
[0009] b. Prepare an organic gel-nanoparticle cluster prepolymer: fully stir and mix an organic polymer gel prepolymer, a curing agent, a light absorbing material and a monodisperse nanoparticle cluster at room temperature to obtain a uniform organic gel-nanoparticle cluster prepolymer, wherein the mass ratio of the organic polymer gel prepolymer, the curing agent, the light absorbing material and the monodisperse nanoparticle cluster is 1:(0.1-0.3):(0.001-0.003):
[0010] (0.2-0.5); wherein the organic polymer gel prepolymer is one of a polyurethane prepolymer, an epoxy resin prepolymer or a polydimethylsiloxane prepolymer; under the action of a corresponding curing agent, cross-linking and curing can be achieved;
[0011] c. Treatment of the substrate surface: Place the substrate in an ethanol bath for ultrasonic washing to remove dust, oil stains and small organic molecules on the surface, and dry it at room temperature to obtain a substrate with a clean surface;
[0012] d. The prepared organic gel-nanoparticle prepolymer is coated on the treated substrate surface and allowed to stand for curing to obtain a coating having an angle-independent structural color, wherein the coating thickness is 200-500 μm.
[0013] Preferably, the nanoparticles in the monodisperse nanoparticle dispersion described in step a are one of polystyrene nanoparticles, polymethyl methacrylate nanoparticles or silica nanoparticles; the particles in the monodisperse nanoparticle dispersion maintain a high degree of monodispersity in the solvent, and the aggregation index (PDI value) is 0.001-0.05.
[0014] Preferably, the particle size of the nanoparticles in the monodisperse nanoparticle dispersion described in step a is 180-350nm, and the submicron particle size ensures that the structural color of the coating is adjustable in the entire visible light range, and the mass fraction of the nanoparticles is 10%-20%; the solvent in the monodisperse nanoparticle dispersion described in step a is one of water or ethanol or a mixture of the two.
[0015] Preferably, the monodisperse nanoparticle clusters described in step a maintain a highly spherical morphology, and the cluster sizes are dispersed in the micrometer scale range of 1-10 μm.
[0016] Preferably, the curing agent described in step b is the corresponding curing agent of the organic polymer gel prepolymer, wherein the curing agent of the polyurethane prepolymer is one of diisocyanate carbamate or diisocyanate urea; the curing agent of the epoxy resin prepolymer is one of ethylenediamine, hexamethylenediamine, diethylenetriamine or triethylenetetramine; and the curing agent of the polydimethylsiloxane prepolymer is diphenylbutyl carbamate.
[0017] Preferably, the light absorbing material in step b is one or a mixture of two or more of nano carbon black, carbon nanotubes, carbon dots or dopamine particles. Black light absorbing materials can effectively eliminate ambient light and incoherent scattered light, which is beneficial to enhance the saturation of the coating structure color.
[0018] Preferably, the stirring speed in step b is 200-300 rpm and the stirring time is 40-80 min.
[0019] Preferably, the substrate described in step c is one of metal, plastic or glass; the ultrasonic washing power described in step c is 500-1000W, and the time is 10-30min.
[0020] Preferably, the coating method in step d is one of scraping, rolling or brushing.
[0021] Preferably, the curing time in step d is 6-12 hours and the curing temperature is 30-60°C.
[0022] The present invention provides a method for preparing a structural color coating, and its further technical solution is that the prepared structural color coating has bright angle-independent structural color, the coating is uniform and has good mechanical stability, chemical stability and scrubbing resistance. Experimental measurements show that the adhesion of the coating can reach above level 1 (GB / T9286-1998), and at the same time, the coating is scrubbed 1600-1800 times by a scrubber without being completely damaged or exposing the bottom.
[0023] Beneficial effects:
[0024] 1. The structural color coating prepared by the present invention has good mechanical stability, chemical stability and washability, and can be widely used in the decoration and protection of the surface of substrates such as metals, plastics, and glass;
[0025] 2. The present invention provides a method for preparing a structural color coating. The entire preparation process is simple, highly compatible, and does not require special post-processing. In addition, the coating does not emit VOCs into the atmosphere during the curing film-forming process, thus meeting the requirements of green and sustainable development.
[0026] 3. The structural color coating prepared by the present invention presents the color generated by the structure, and will not cause the problems of photo-oxidation and photo-bleaching. At the same time, the structural color also avoids the environmental pollution caused by chemical dyeing, and is green and environmentally friendly.
[0027] 4. The angle-independence of the structural color of a structural color coating prepared by the present invention is derived from the isotropic spherical symmetric structure of monodisperse nanoparticle clusters. The long-range and short-range ordered lattice structures in the particle clusters ensure the brightness and saturation of the structural color. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a SEM image of the monodisperse nanoparticle clusters prepared in Example 1;
[0029] Figure 2 The optical image and reflection spectrum of the blue structural color coating prepared in Example 1;
[0030] Figure 3 This is a SEM image of the blue structural color coating prepared in Example 1;
[0031] Figure 4 Optical images of the blue structural color coating prepared in Example 1 at different bending angles;
[0032] Figure 5 The (a) chemical stability, (b) mechanical stability, and (c) scrub resistance test graphs of the blue structural color coating prepared in Example 1;
[0033] Figure 6Optical images and reflection spectra of the green structural color coating prepared in Example 2;
[0034] Figure 7 Optical images and reflection spectra of the red structural color coating prepared in Example 3. DETAILED DESCRIPTION
[0035] The present invention is described below by means of specific embodiments, but the present invention is not limited to the following embodiments, which are only intended to provide a better understanding of the present invention rather than to limit the scope of protection of the present invention.
[0036] Example 1
[0037] The inlet temperature of the spray drying equipment, the peristaltic pump feed rate and the air flow rate were set to 130°C, 10 mL / h and 30 L / h respectively. After the parameters of the equipment were stabilized, an ethanol dispersion of silica nanoparticles with a particle size of 180 nm, a PDI value of 0.02 and a mass fraction of 20% was introduced. Under the action of the high-temperature airflow, the solvent in the dispersion was quickly removed, and the silica nanoparticles spontaneously assembled into spherical monodisperse nanoparticle clusters. From the SEM image of Figure (1), it can be seen that the spherical monodisperse nanoparticle clusters are assembled from silica nanoparticles arranged in a long-range ordered and short-range ordered lattice structure, and the cluster size is scattered in the micrometer scale range of 1-8 μm. 10g of polydimethylsiloxane prepolymer, 1g of diphenylcarbamate curing agent, 0.01g of nano carbon black and 5g of pre-prepared monodisperse silica nanoparticle clusters were weighed in a 50mL beaker using an analytical balance. The mixture was stirred continuously for 80min at 200rpm at room temperature to obtain a uniform organogel-nanoparticle cluster prepolymer. The purchased plastic substrate was placed in an ethanol bath ultrasonic cleaner with a power of 500W and ultrasonically cleaned for 10 minutes to remove dust, oil stains and small organic molecules on the surface of the substrate. The substrate was dried at room temperature for later use. The prepared organogel-nanoparticle cluster prepolymer was coated on the treated plastic substrate surface by scraping. The coating thickness was 300μm. The coating was then cured at 30℃ for 12h to obtain a structural color coating. The coating exhibited a blue structural color as shown in Figure (2). As can be seen from the SEM image, spherical nanoparticle clusters of different sizes and monodisperse nanoparticles orderly arranged in the clusters are distributed in the coating, as shown in Figure (3). Based on the isotropic optical properties of spherical nanoparticle clusters and highly ordered assembly structures, the prepared structural color coating has saturated and bright colors and exhibits angle-independent characteristics, as shown in Figure (4). After immersion in solutions of different pH values for 48 hours, the morphology, structure and color of the coating were not destroyed, showing good chemical stability, as shown in Figure (5a). Experimental measurements have shown that the coating has good mechanical stability, and the adhesion of the coating can reach level 0 (GB / T9286-1998), as shown in Figure (5b). At the same time, the coating has good scrubbing resistance. After 1,800 reciprocating scrubbings by a scrubber, the coating was still not completely damaged or exposed, as shown in Figure (5c).
[0038] Example 2
[0039] The inlet temperature of the spray drying equipment, the peristaltic pump feed rate and the air flow rate were set to 120°C, 25mL / h and 40L / h respectively. After the parameters of the equipment were stabilized, an alcohol-water dispersion of polystyrene nanoparticles with a particle size of 250nm, a PDI value of 0.001 and a mass fraction of 10% was introduced. Under the action of the high-temperature airflow, the solvent in the dispersion was quickly removed, and the polystyrene nanoparticles spontaneously assembled into spherical monodisperse nanoparticle clusters, and the cluster size was dispersed in the micrometer scale range of 2-10μm. 10g of polyurethane prepolymer, 2g of diisocyanate urethane curing agent, 0.01g of carbon nanotubes, 0.01g of carbon dots and 3g of pre-prepared monodisperse polystyrene nanoparticle clusters were weighed in a 50mL beaker with an analytical balance, and stirred continuously for 60min at a speed of 200rpm at room temperature to obtain a uniform organogel-nanoparticle cluster prepolymer. The purchased glass substrate was placed in an ethanol bath ultrasonic cleaner with a power of 800W and ultrasonically cleaned for 20 minutes to remove dust, oil stains and small organic molecules on the surface of the substrate, and then dried at room temperature for later use. The prepared organic gel-nanoparticle cluster prepolymer was coated on the treated glass substrate surface by brushing, with a coating thickness of 200μm, and then placed in an environment of 40℃ for curing for 8h to obtain a structural color coating, which exhibits a green structural color as shown in Figure (6). The coating has good mechanical stability and the adhesion of the coating can reach level 1 (GB / T9286-1998). At the same time, the coating has good scrubbing resistance. After 1600 reciprocating scrubbings by the scrubber, the coating is still not completely damaged and the bottom is not exposed.
[0040] Example 3
[0041] The inlet temperature of the spray drying equipment, the peristaltic pump feed rate and the air flow rate were set to 100°C, 30mL / h and 50L / h respectively. After the parameters of the equipment were stabilized, an aqueous dispersion of polymethyl methacrylate nanoparticles with a particle size of 350 nanometers, a PDI value of 0.05 and a mass fraction of 20% was introduced. Under the action of the high-temperature airflow, the solvent in the dispersion was quickly removed, and the polymethyl methacrylate nanoparticles spontaneously assembled into spherical monodisperse nanoparticle clusters, and the cluster size was dispersed in the micrometer scale range of 1-7μm. 10g of epoxy resin prepolymer, 3g of ethylenediamine curing agent, 0.02g of carbon dots, 0.01g of dopamine particles and 2g of pre-prepared monodisperse polymethyl methacrylate nanoparticle clusters were weighed in a 50mL beaker using an analytical balance, and stirred continuously for 40min at a speed of 300rpm at room temperature to obtain a uniform organic gel-nanoparticle cluster prepolymer. The purchased iron sheet substrate was placed in an ethanol bath ultrasonic cleaner with a power of 1000W and ultrasonically cleaned for 30 minutes to remove dust, oil stains and small organic molecules on the surface of the substrate, and then dried at room temperature for use. The prepared organic gel-nanoparticle cluster prepolymer was coated on the surface of the treated iron sheet substrate by roller coating, with a coating thickness of 500μm. It was then placed in an environment of 60℃ for curing for 6h to obtain a structural color coating, which exhibited a red structural color as shown in Figure (7). The coating was experimentally determined to have good mechanical stability, and the adhesion of the coating could reach level 1 (GB / T9286-1998). At the same time, the coating has good scrubbing resistance. After 1700 reciprocating scrubbings by the scrubber, the coating was still not completely damaged or exposed.
Claims
1. A method for preparing a structural color coating, the specific steps of which are as follows: a. Preparation of monodisperse nanoparticle clusters: using a spray drying device to quickly remove the solvent in the monodisperse nanoparticle dispersion to obtain spherical monodisperse nanoparticle clusters distributed in micrometer scale; wherein, The parameters of the spray drying equipment were set as 100-130°C inlet temperature, 10-30mL / h peristaltic pump feed rate, and 30-50L / h air flow rate; b. preparing an organic gel-nanoparticle cluster prepolymer: fully stirring and mixing an organic polymer gel prepolymer, a curing agent, a light-absorbing material and a monodisperse nanoparticle cluster to obtain a uniform organic gel-nanoparticle cluster prepolymer, wherein the mass ratio of the organic polymer gel prepolymer, the curing agent, the light-absorbing material and the monodisperse nanoparticle cluster is 1:(0.1-0.3):(0.001-0.003):(0.2-0.5); wherein the organic polymer gel prepolymer is one of a polyurethane prepolymer, an epoxy resin prepolymer or a polydimethylsiloxane prepolymer; c. Treatment of the substrate surface: placing the substrate in an ethanol bath for ultrasonic washing to remove dust, oil stains and small organic molecules on the surface, and drying to obtain a substrate with a clean surface; d. The prepared organic gel-nanoparticle prepolymer is coated on the treated substrate surface and allowed to stand for curing to obtain a coating having an angle-independent structural color, wherein the coating thickness is 200-500 μm.
2. The preparation method according to claim 1, characterized in that The nanoparticles in the monodisperse nanoparticle dispersion in step a are one of polystyrene nanoparticles, polymethyl methacrylate nanoparticles or silicon dioxide nanoparticles; the aggregation index (PDI) of the monodisperse nanoparticle dispersion is 0.001-0.
05.
3. The preparation method according to claim 1, characterized in that The particle size of the nanoparticles in the monodisperse nanoparticle dispersion described in step a is 180-350nm, and the mass fraction of the nanoparticles is 10%-20%; the solvent in the monodisperse nanoparticle dispersion described in step a is water or ethanol or a mixture of the two.
4. The preparation method according to claim 1, characterized in that The monodisperse nanoparticle clusters described in step a maintain a highly spherical morphology, and the cluster sizes are dispersed in the micrometer scale range of 1-10 μm.
5. The preparation method according to claim 1, characterized in that The curing agent described in step b is the corresponding curing agent of the organic polymer gel prepolymer, wherein the curing agent of the polyurethane prepolymer is one of diisocyanate carbamate or diisocyanate urea; the curing agent of the epoxy resin prepolymer is one of ethylenediamine, hexamethylenediamine, diethylenetriamine or triethylenetetramine; the curing agent of the polydimethylsiloxane prepolymer is diphenylbutyl carbamate.
6. The preparation method according to claim 1, characterized in that The light absorbing material described in step b is one or a mixture of two or more of nano carbon black, carbon nanotubes, carbon dots or dopamine particles.
7. The preparation method according to claim 1, characterized in that The stirring speed described in step b is 200-300rpm, and the stirring time is 40-80min.
8. The preparation method according to claim 1, characterized in that The substrate described in step c is one of metal, plastic or glass; the ultrasonic cleaning power described in step c is 500-1000W, and the time is 10-30min.
9. The preparation method according to claim 1, characterized in that The coating method described in step d is one of scraping, rolling or brushing.
10. The preparation method according to claim 1, characterized in that The curing time in step d is 6-12 hours, and the curing temperature is 30-60°C.
Citation Information
Patent Citations
A kind of hydrophobic structural color coating and preparation method thereof
CN104725919B
A method for preparing structural color coatings using microspheres
CN107201690B
Photonic crystal structure color coating with high strength and continuous and controllable color as well as preparation and application of photonic crystal structure color coating
CN114958182A
Waterborne polyurethane structure color waterproof coating material, preparation method and application thereof
CN113072867A
Preparation method of colloidal particle three-dimensional conformal structural color coating material
CN118515995A